Content and Enforcement of the Right to Education in Higher Education - Does Being European Make a Difference? - Szappanyos, Melinda (Pécs journal of international and European law, 2014)
Nine words represent the basic difference in the content of the right to education in higher education between the Member States of the Council of Europe and non-European States on international level. First, the content of the right to education in higher education should be drawn out, with the help of international documents mentioning the right to education. After clarifying the content, this paper intends to collect together, briefly analyse and compare the opportunities of enforcement of the right to education on national and international level, giving priority to the latter. To be able to give a fairly detailed picture and more relevant information a comparison seems to be beneficial. Therefore, definitions and opportunities of enforcement will be collected and compared in European higher education systems and in the Republic of Korea.